Analysis of risk factors for acute cerebral infarction in patients with intracranial tuberculosis - Xiao-Shan Huang; Xiao-Wei Qiu; An-Long Wang; Fei He; Yi-Jing Wang (Frontiers in Neurology)
ObjectiveAcute cerebral infarction is a common complication of intracranial tuberculosis (TB), causing irreversible damage to brain tissue and significantly affecting patient prognosis. This study aims to explore the risk factors associated with acute cerebral infarction in patients with intracranial tuberculosis.MethodsWe retrospectively analyzed data from eligible intracranial TB patients treated at our hospital between January 2020 and March 2023. Based on MRI findings, patients were categorized into a cerebral infarction group and a non-infarction group. Clinical data, cerebrospinal fluid (CSF) examinations, and imaging features (such as hydrocephalus, cerebral arteritis, and meningeal thickening) were compared between the two groups. Binary logistic regression analysis was used to identify risk factors for acute cerebral infarction in patients with intracranial TB.ResultsA total of 102 patients were included, with 24 in the cerebral infarction group and 78 in the non-infarction group. Male patients accounted for 87.5% in the infarction group and 58.3% in the non-infarction group. Patients with a Glasgow Coma Scale (GCS) score of 3–10 accounted for 45.8% in the infarction group compared to 15.4% in the non-infarction group. The incidence of hydrocephalus, cerebral arteritis, and meningeal thickening was significantly higher in the infarction group (37.5, 54.2, and 79.2%, respectively) compared to the non-infarction group (6.4, 6.4, and 43.6%, respectively) (p < 0.05). The parenchymal type of intracranial TB was less frequent in the infarction group (20.8%) than in the non-infarction group (56.4%), while the mixed type was more frequent in the infarction group (62.5%) compared to the non-infarction group (26.9%) (p < 0.05). Patients with meningeal thickening involving the cisterns and basal cisterns had a higher risk of cerebral infarction (p < 0.05). Multivariate binary logistic regression analysis revealed that male sex (OR = 13.56; 95% CI 1.25–38.30) and cerebral arteritis (OR = 19.32; 95% CI 0.94–37.64) were independent risk factors for cerebral infarction in intracranial TB patients.ConclusionMale sex and the presence of cerebral arteritis are independent risk factors for acute cerebral infarction in patients with intracranial tuberculosis.